2013
DOI: 10.1136/jnnp-2012-304306
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier destruction determines Fisher/Bickerstaff clinical phenotypes: an in vitro study

Abstract: Only the sera obtained from BBE patients destroyed BBB and it might explain the phenotypical differences between BBE and MFS. BBE sera disrupted BBB, possibly via the autocrine secretion of MMP-9 from BBB-composing endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 40 publications
1
21
0
1
Order By: Relevance
“…In the present study, we used conditionally immortalised human BNB-derived endothelial cells to analyse the effects of the sera from patients with MMN on the impairment of the BNB function 14. We have also previously reported that VEGF disrupts the BNB and that sera obtained from patients with Bickerstaff's brainstem encephalitis and Miller Fisher syndrome did not influence the barrier function in the same in vitro BNB model 21 28. Our present study is the first to demonstrate that the sera from patients with MMN can disrupt the BNB.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, we used conditionally immortalised human BNB-derived endothelial cells to analyse the effects of the sera from patients with MMN on the impairment of the BNB function 14. We have also previously reported that VEGF disrupts the BNB and that sera obtained from patients with Bickerstaff's brainstem encephalitis and Miller Fisher syndrome did not influence the barrier function in the same in vitro BNB model 21 28. Our present study is the first to demonstrate that the sera from patients with MMN can disrupt the BNB.…”
Section: Discussionmentioning
confidence: 88%
“…The sequences of human primers for MMP-2 , MMP-9 and G3PDH have been previously described 26. A Stratagene Mx3005P instrument (STRATAGENE, Cedar Greek, Texas, USA) was used to perform the quantitative real-time PCR analyses, and the relative quantity of each molecule was calculated according to the R v =R Gene /R GAPDH using a software program as previously described 26…”
Section: Methodsmentioning
confidence: 99%
“…It suggests that the underlying pathological mechanisms of MMN may be rather different from those of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). The authors’ group has already reported that sera from patients with Bickerstaff's brainstem encephalitis and Miller Fisher syndrome did not influence the barrier function in the PnMECs model 4. The effects of the sera from CIDP patients on the BNB function of the same model is needed to clarify whether such disruptive effects are specifically seen in MMN sera or not.…”
mentioning
confidence: 99%